Cost-effectiveness of endobronchial valve therapy for severe emphysema: a model-based projection based on the VENT study - Pietzsch, Jan B.; Garner, Abigail; Herth, Felix (Respiration, 2014)
Background: Endobronchial valve (EBV) therapy is an innovative treatment that has been shown to be safe and effective in selected subgroups of patients with severe emphysema. Objectives: The objective of our study was to assess the cost-effectiveness of EBV therapy compared to the medical management of patients with high heterogeneity, complete fissures and lobar exclusion in the context of the German health-care system. Methods: Clinical data from a subset of VENT (Endobronchial Valve for Emphysema Palliation Trial) provided information about clinical events, health-related quality of life, and disease staging for 12 months. This information was subsequently used to project long-term disease progression, mortality, and health resource utilization. We computed the 5- and 10-year incremental cost-effectiveness ratio (ICER) in euros per quality-adjusted life year (QALY). Costs and effects were discounted at 3% per year. Results: EBV therapy led to clinically meaningful disease restaging at 12 months (37.8% of the cohort improved staging, compared to 0% in the controls). Over 5 years, EBV therapy was projected to increase survival from 66.4 to 70.7%, and to add 0.22 QALYs. Costs were estimated to increase by EUR 10,299, resulting in an ICER of EUR 46,322 per QALY. Over 10 years, 0.41 QALYs were gained at an additional cost of EUR 10,425, yielding an ICER of EUR 25,142 per QALY. Conclusions: Our model-based analysis suggests that EBV therapy leads to clinically meaningful changes in disease staging and progression when compared to medical management, with resulting gains in unadjusted and quality-adjusted life expectancy. Our results indicate that EBV therapy is cost-effective in the German health-care system.